3D printing system: an innovation for small-scale manufacturing in home settings? – early adopters of 3D printing systems in China. Issue 20 (17th October 2016) - Wang, Qingfeng; Sun, Xu; Cobb, Sue; Lawson, Glyn; Sharples, Sarah
Abstract : This study investigates Chinese consumers' adoption of the innovative 3D printing systems for small-scale manufacturing in home settings. Empirical studies were conducted in a survey with 256 participants. The number of significant determinants that affect an individual's decision to adopt 3D printing systems has been identified by applying a model that integrates the Technology Acceptance Model and Innovation Diffusion Theory. A number of moderation effects of demographic variables (e.g. gender, design background) on the association between motivational variables and participants' adoption have also been analysed with factor analysis, structural equation modelling and hierarchical regression. Our results shed some light on the characteristics of early adopters of home 3D printing systems in China. This study contributes to the early understanding of Chinese consumers' adoption of innovative 3D printing systems.